Estimating The Role Of Bromalain In The Protection Effect Of Alzheimer’s Disease Induced By Scopolamine (International Journal of Environmental Sciences, 2025)
The current study was aimed to estimate the role of bromalain in the Protection Effect of Alzheimer’s Disease induced by scopolamine via evaluating the antioxidant activity and anti-inflammatory activity of bromalain. For the study, 25 adult female rats were used, which were obtained from the animal house at the Veterinary Medicine College of Tikrit University. Between 10 and 12 weeks of age, the animals weighed an average of 207 grams, with a range of 181 to 204 grams. Between August 29, 2024, and September 11, 2024, the experiment was conducted at the College of Veterinary Medicine's animal home at Tikrit University. Animals were divided into five main groups (each group consisted of 5 adult female). The findings showed that the levels of AChE in positive group demonstrated a significant (P≤0.05) increased compared to the control group. in the treated groups, the AChE and ABE1 – 42 levels continue to show elevation compared to the control group, but less than positive group. The levels of ACH showed significant decreased in G2 group (P≤0.05) in contrast to the untreated group. in the treated groups, the ACH levels showed non-significant (P≤0.05) differences compared to the control group. The findings showed that the levels of GSH in positive group demonstrated a significant (P≤0.05) decreased in G2 group in contrast to the untreated group. in the treated groups, the GSH levels showed significant (P≤0.05) increased in contrast to the untreated group. The levels of IL–1 and BCS showed significant increase in positive group (P≤0.05) in contrast to the untreated group. in the treated groups, the IL–1 levels showed significant (P≤0.05) decreased in contrast to the untreated group. It is concluded that bromalain has an effective and protective role against the harmful effects of scopolamine, which causes Alzheimer's disease in mice.